Influência do alongamento da cadeia muscular respiratória na postura rã do método de reeducação postural global (RPG) sobre as respostas cardiorrespiratórias - Moreno, Marlene Aparecida (2007)
Stretching by the global postural re-education method (GPR) has been widely used as a physical therapeutic procedure for postural alterations, but its action on the cardio-respiratory system has been little documented. However, scientific evidence is necessary to validate it as an alternative treatment. Within this context, three studies were carried out with the objective of verifying the effect of stretching the respiratory muscle chain in the open-arm, open hip joint angle posture by the GPR method on cardio-respiratory responses. Twenty young (22.7±2.5 years old), healthy, sedentary (VO2max: 30.2±4.3 mL.kg.min-1) men with BMI = 25.3±1.5 kg/m2 were studied, divided at random into two groups of ten: the control group (CG) that did not take part in the stretching and the group submitted to treatment (GPR-G). The intervention consisted of two weekly stretching sessions, each of 30 min, for eight weeks, giving a total of 16 sessions. In the first study, the maximal respiratory pressure and the respiratory coefficient were assessed by way of a manovacuometer and thoracoabdominal cirtometry, respectively. Only the GPR-G presented greater values for inspiratory (IPmax) and expiratory (EPmax) maximal pressures and for axillary, xyphoid and abdominal cirtometry after the intervention period. The results showed that the method caused a beneficial effect on respiratory muscle force and on thoracoabdominal mobility, contributing to an improvement in respiratory mechanics. In the second study, pulmonary function was assessed by spirometry. The manoeuvres of slow vital capacity (SVC), forced vital capacity (FVC) and maximal voluntary ventilation (MVV) were carried out. The results showed there was a significant increase in the values for SVC, inspiratory capacity (IC), FVC, forced expiratory volume in the first second (FEV1) and MVV for the GPR-G after the training period, providing evidence that the proposed stretching was efficient in promoting an increase in pulmonary capacity and volume. In the third study, the effect of stretching on the autonomic modulation of the heart rate (HR) and on the ventilatory and metabolic variables was assessed at rest and during the cardio-pulmonary exercise test respectively. The ventilatory and metabolic variables were captured using an automatic metabolic system and the HR using a one-channel heart monitor. The exercise test was carried out using a cycle ergometer, with 20 to 25 W/min increments up to physical exhaustion. Intervention did not change the variables studied either at rest or during the cardio-pulmonary exercise test, for either of the groups. These results showed that the respiratory muscle chain stretching exercise did not promote any adaptations with respect to HR neither at rest and the ventilatory and metabolic variables during the exercise, which could be attributed to the noninvolvement of the major muscle groups in the type of protocol used. Finally, the results obtained in the three studies gave evidence that stretching the respiratory muscle chain by the GPR method was efficient in promoting an increase in respiratory muscle strength, thoracoabdominal mobility and pulmonary function, reflecting in an increase in respiratory mechanics, this fact being attributable to the specificity of the training. In this way, the findings of the present study, reinforce the importance of the GPR method in the maintenance of the functional capacity of the respiratory chain muscles, suggesting that it could be used as an alternative treatment for dysfunctions of the respiratory mechanics.